AN EXPERIMENTAL INVESTIGATION FOR THE SYNTHESIS OF OXALIC ACID BY NITRIC ACID OXIDATION OF DATES FRUIT AND SYRUP (Journal of Engineering, 2003)
An experimental investigation was conducted to study the various parameters affecting the production of oxalic acid by the action of concentrated nitric acid on carbohydrates. Two feedstocks were studied, viz., dates fruit and dates syrup. The study also covered the effect of the amount of nitric acid and catalyst used in addition to employing two acid concentrations (67 wt.% and 98 wt.% acid). The results showed that when using 67 wt.% nitric acid, dates syrup was best suited as a raw material. And the best amount of nitric acid and V₂O, catalyst were in the ratio of 150 mls: 25 mg per 50 g feedstock. When using 98 wt.% nitric acid, no catalyst was required for the reaction and the reaction proceeded violently with the evolution large amount of the nitrogen oxides